Auriculotherapy as an integrative and complementary practice to health care anxiety: an integrative review (Research, Society and Development, 2023)
Auriculotherapy is a natural therapy that uses the stimulation of specific points of the ear, a microsystem of the human body, generating stimulation of the cerebral cortex that, by reflex, acts balancing the organism, providing physical, mental and emotional well-being. The aim of this study was to carry out an integrative review on the clinical evidence of auriculotherapy in anxiety care as an integrative and complementary health practice; databases: GOOGLE ACADÊMICO, PUBMED, BVS and SCIELO were used to survey the literature. A careful selection of scientific articles was carried out through the inclusion and exclusion criteria adopted, with the selection of eight articles of the clinical trial type, with 75% (6/8) characterized as randomized and 25% (2/8) defined as non-randomized. The analysis of the studies allowed inferring that the practice of auriculotherapy presents statistically significant results in the complementary treatment of anxiety, regardless of the auricular pressure material used, based on the methodological approaches adopted. It is important to highlight that the investigated randomized clinical trials used different samples with a medium to high degree of anxiety, such as students, pre-delivery women, health professionals and the prison system. Additionally, auriculotherapy has advantages such as: easy application, low cost, minimal side effects and use of non-invasive materials. This fact allows the population to have access to this integrative and complementary therapy that contributes to the integral health of the user, in particular, of the Unified Health System.